ПЕРЕХОД ЧЕРНОМОРСКОЙ КАЗАЧЬЕЙ ФЛОТИЛИИ К ТАМАНИ В АВГУСТЕ 1792 ГОДА (Zaporizhzhia Historical Review, 2021)
The article studies the history of the Black Sea flotilla move to Tamaní in August of 1792. Acording to the author the flotilla was not ready for the transference, so the move to Tamaní turned out the severe trial both for the vessels and their crews.